The PERT System: An Appraisal of Program Evaluation Review Technique - Roman, Daniel D. (Academy of Management Journal, 1962)
Assesses the simplification of the Program Evaluation Review Technique, designed for managerial science course. Discussion on corporate planning and management goals; Analysis of different management tools, such as scheduling and productivity index.